On the design of a helicopter rotor blades exposed to the wind flow - Kargaev, M.V.; Ignatkin, Y.M. (My University, 2019)
The paper presents methods for calculating bending stresses in the rotor blade of a helicopter blown by a wind flow. The data obtained using the methods set out in this paper can be used in the design of the rotor blades and the determination of safe operation to ensure the required reserves for operational wind speeds. For the problem in the linear formulation, convenient calculation formulas for calculating deflections, angles of rotation and bending moments (stresses) directly through their values for the "rigid" blade are obtained. For the problem in the nonlinear formulation, a simple-to-implement computational scheme for solving the initial nonlinear equation of loading of the blade based on the method of successive perturbations of the parameters of V. V. Petrov is obtained. The results of calculations made for the tested rotor blades of the helicopter.